Potential Therapeutic Agents for Feline Calicivirus Infection - Tulio M. Fumian; Daniel Enosi Tuipulotu; Natalie E. Netzler; Jennifer H. Lun; Alice G. Russo; Grace J. H. Yan; Peter A. White (Viruses, 2018)
Feline calicivirus (FCV) is a major cause of upper respiratory tract disease in cats, with widespread distribution in the feline population. Recently, virulent systemic diseases caused by FCV infection has been associated with mortality rates up to 50%. Currently, there are no direct-acting antivirals approved for the treatment of FCV infection. Here, we tested 15 compounds from different antiviral classes against FCV using in vitro protein and cell culture assays. After the expression of FCV protease-polymerase protein, we established two in vitro assays to assess the inhibitory activity of compounds directly against the FCV protease or polymerase. Using this recombinant enzyme, we identified quercetagetin and PPNDS as inhibitors of FCV polymerase activity (IC50 values of 2.8 μM and 2.7 μM, respectively). We also demonstrate the inhibition of FCV protease activity by GC376 (IC50 of 18 µM). Using cell culture assays, PPNDS, quercetagetin and GC376 did not display antivirals effects, however, we identified nitazoxanide and 2′-C-methylcytidine (2CMC) as potent inhibitors of FCV replication, with EC50 values in the low micromolar range (0.6 μM and 2.5 μM, respectively). In conclusion, we established two in vitro assays that will accelerate the research for FCV antivirals and can be used for the high-throughput screening of direct-acting antivirals.